Ordinary differential equations : a practical guide - Schroers, Bernd J. (New York : Cambridge University Press, 2011)
'Ordinary Differential Equations' introduces key concepts and techniques in the field and shows how they are used in current mathematical research and modelling. It deals specifically with initial value problems, including mathematics, physics, computer science, statistics and biology.
Includes bibliographical references (p. 116) and index.
Keywords: Differential equations; Combinatorial structures; Moment-angle complexes; Half-dimensional torus actions